Effect of testicle postmortem storage on goat frozen-thawed epididymal sperm quality as a tool to improve genebanking in local breeds. (17th December 2013) - Turri, F.; Madeddu, M.; Gliozzi, T. M.; Gandini, G.; Pizzi, F.
<x content-type="archive" xml:space="preserve">Abstract</x> The interest to develop assisted reproductive technologies and cryobanking for farm animal genetic resource conservation has recently increased. However, cryopreservation for ex-situ management of genetic diversity sometimes is not routinely feasible, owing to the lack of facilities (AI centres, laboratories) and expertise near the local breed farming area. In these cases, epididymal sperm obtained from slaughtered or castrated animals, associated with the possibility of managing rather long periods between animal death, sperm recovery and freezing, would increase the opportunities to create semen storages. This investigation addresses the pre-freeze/post-thaw quality of goat epididymal sperm as a function of testicle storage temperature (environment or +5°C) and time elapsed between animal's death and sperm recovery (0, 24, 48, 72 h) to establish the optimal protocols for the recovery and cryopreservation of epididymal sperm in this species. Testicles of 50 mature bucks collected at the abattoir were divided in two groups: half of the testicles (n=50) were transported to the laboratory at environment temperature (E), whereas the remaining half (n=50) at a refrigeration temperature (R) of +5°C. In the two groups (E) and (R), one testicle from each pair was processed after slaughter forming the time 0 groups (0E and 0R). The contralateral testicle was processed after 24, 48 or 72 h of storage, at the corresponding temperature. Sperm motility and kinetic parameters, viability and morphology were assessed in pre-freeze and post-thaw samples. Until 48 h postmortem, both E and R temperatures are able to maintain good pre-freeze epididymal sperm quality. After 48 h postmortem, R temperature is fundamental to reduce epididymal sperm quality decay in pre-freeze samples. Moreover, testicle refrigeration also has a positive impact on post-thaw samples, allowing a lower decline through time considering total motility, kinetics parameters, sperm viability and sperm abnormalities. Therefore, when sperm cryopreservation is not immediately practicable, goat testicles should be transported and stored at 5°C up to a maximum of 48 h postmortem to ensure an acceptable sperm quality.